Biopolymers in Medical Implants: A Brief Review. (2017) - Rebelo, Rita; Fernandes, Margarida; Fangueiro, Raul
Abstract: Biopolymers have been established as a promising class of materials with a wide range of applications, of which medicine stands out. Characteristics such as biocompatibility, biodegradation and non-cytotoxicity make these material excellent candidates to be used in implantable materials. This review examines the main properties of biopolymers, as well as the potential of different biopolymers, including polylactic acid (PLA), silk and chitosan, for application in implantable medical devices.